Bonaparte Printzearen inguruko hizkuntz eztabaidak - Ricardo Gómez (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1992)
The object of this essay is to give an account of the linguistic polemic that arose towards the end of the last century between Prince L.-L. Bonaparte and other Basque scholars, like W. J. van Eys, J. Vinson and A. Luchaire. This aspect has received little attention from students of Bonaparte's work. The author of this essay attempts to develop certain topics of discussion wich at the time meant an advance in research on the Basque language, as well as to explain the relationship of these Basque scholars with the linguistics theories and methods of their time, and especially with the influence of Schleicher and comparative grammar in general.